Women as consumers of maternity care: measuring "satisfaction" or "dissatisfaction"? - Redshaw, M (2008)
The measurement of "satisfaction" has been intrinsic to the models of evaluation of health care. However, a thoughtful approach to its use has not always been evident in which this concept is understood to represent a complex group of theoretical constructs involving attitudes, expectations, and perceptions that may be both positive and critical. These constructs require investigation and evaluation using recognized and developed methodologies. At the same time the importance of listening to patients and to women and their partners in evaluating and carrying out research on maternity care cannot be underestimated if the instruments used are to have construct and face validity. Qualitative data of this kind have a dual function of contributing to a more complex picture of women's experience and of suggesting that researchers need to explore the issues related to "dissatisfaction" at least as much as those arising from a positive overall view of care.